THE INFLUENCE OF SERVICE FEATURES AND EASE OF USE OF M-BANKING ON THE SATISFACTION OF M-BANKING USERS - Lius, Diana (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2022)
In this modern era, the development of technology is very rapid. This technological development was also followed by the banking world in Indonesia where banks in Indonesia began to launch digital banking products such as M-banking (Mobile Banking). With the features in M-banking, customers can make transactions easily without the need to come directly to the bank. The M-banking service provided is 24/7, meaning that the bank offers a seven-day service for twenty-four hours and provides easy service without time restrictions. The purpose of this study is to determine The Influence of Service Features and Ease of Use of M-banking on The Satisfaction of M-banking Users at PT. Bank Mestika Dharma, Tbk. The object of this study is M-banking user at headquarters of PT. Bank Mestika Dharma, Medan. The sample used was 110 customers calculated by the (Hair, et al 2015) formula. The sampling technique used was purposive sampling and the data collection method in this study used Quantitative method by distributing questionnaires to respondents measured by a likert scale.